The Rural under the Common Agricultural Policy of the European Union: Sustainable Rural Development aspects of Pillar II in Finland and Estonia - Kull, Michael; Voutilainen, Olli; Christopoulos, Stamatios; Reimets, Ramon (The International Journal of Sociology of Agriculture and Food, 2014)
National ministries of agriculture and competent EU authorities currently have the reforms of the EU’s Common Agricultural Policy (CAP) high on their agendas in terms of planning and designing the upcoming programmatic period. Also subjected to this debate are the allocation of the budget to each pillar and their territorial impact. The interest of this article lies with two interrelated aspects. The first comprises an overview of the Pillar II budget and how this is allocated within EU member states. The second considers how these measures relate and contribute to the improvement of the socio-economic situation and the state of the environment in rural areas of the EU in general, and in Estonia and Finland in particular. Seemingly, the way funding has been allocated thus far, with a heavy focus on agriculture and directly related activities, is not appropriately suited to facilitate a holistic improvement of the state of rural areas of the EU, while it does not reflect the contemporary economic transition processes in these areas. In terms of protection of the agri-environment, Finland exhibits an unprecedented coverage of areas under environmental support measures, as a Pillar II component, while implementation of the same policy in Estonia results currently in the coverage of less than half of the potential areas. The imbalances in the two countries in terms of actual financial support per hectare are also considerable. To facilitate sustainable development in such areas as a whole, policy streaming should not be broken down into objectives to be reached via broad actions that address particular sectors, and it should not attend to the satisfaction of sectoral interests. Rural areas and their economies, in terms of sustainable development, should be approached in an integrated manner, enabling this process to advance in a holistic and territorial fashion, taking into account all the necessary dimensions of sustainability.